Innovation in General Purpose Technologies : How Knowledge Gains when It Is Shared - Teichert, Nina (KIT Scientific Publishing, 2012)
This book tackles the different aspects of the creation and transmission of knowledge in the context of the characteristics of a general purpose technology. Nanotechnology is investigated as showcase example. Particular emphasis is put on the role of the composition of knowledge as well as the corresponding knowledge spillovers on the one hand and on the concrete impact of collaboration and knowledge sharing in innovator networks on the other hand.